Olfactory Ecto-Mesenchymal Stem Cell-Derived Exosomes Ameliorate Experimental Colitis via Modulating Th1/Th17 and Treg Cell Responses - Tian, Jie; Zhu, Qiugang; Zhang, Yidan; Bian, Qianying; Hong, Yue; Shen, Ziwei; Xu, Huaxi; Rui, Ke; Yin, Kai; Wang, Shengjun (Frontiers in Immunology, 2020)
Olfactory ecto-mesenchymal stem cells (OE-MSCs) are a novel population of resident stem cells in the olfactory lamina propria with strong immunosuppressive function. Exosomes released by MSCs are considered to carry various mRNAs, microRNAs and proteins from cells and function as an extension of MSCs. However, it remains unclear whether exosomes derived from OE-MSCs (OE-MSCs-Exos) possess any immunoregulatory functions. In this study, we found that OE-MSCs-Exos possessed strong suppressive function in CD4+T cell proliferation, accompanied by reduced IL-17, IFN-γ and enhanced TGF-β, IL-10 secreted by T cells. In experimental colitis mice, treatment of OE-MSCs-Exos markedly alleviated the severity of disease, and Th1/Th17 subpopulations were remarkably reduced whereas Treg cells were increased after OE-MSCs-Exos treatment. Mechanistically, OE-MSCs-Exos were demonstrated to inhibit the differentiation of Th1 and Th17 cells, but promote the induction of Treg cells in vitro. Taken together, our findings identified a novel function of OE-MSCs-Exos in regulating T-cell responses, indicating that OE-MSCs-Exos may represent a new cell-free therapy for the treatment of IBD and other inflammatory diseases.